Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.